Tax evasion and financial development in ASEAN-5 - Habibullah, Muzafar Shah; Abdul Hamid, Baharom; Din, Badariah; Ibrahim, Mansor (Faculty of Management and Economics, Universiti Pendidikan Sultan Idris and Penerbit Universiti Pendidikan Sultan Idris, 2017)
The estimated total tax evasion as reported by the Tax Justice Network in 2011 is in the excess of USD3.1 trillion or about 5.1% of world's GDP. Tax evasion is a crime and tax revenue losses have negative consequences to the government ability to fueled economic growth by providing enough public infrastructure and other services. In this study we have estimated the share of tax evasion to the official economy for five ASEAN economies, namely; Indonesia, Malaysia, the Philippines, Singapore and Thailand for the period 1980-2013. Tax evasion was calculated from the estimated size of the shadow economy using the modified-cash-deposits-ratio (MCDR) approach suggested by Pickhardt and Sardia (2011). We investigate the contention made by Blackburn et al. (2012) and Bose et al. (2012) that financial development can mitigate tax evasion - higher level of financial development lead to lower level of tax evasion. Employing the pooled mean group estimator (PMG), our results show that there is a non-linear long-run relationship between tax evasion and financial development in ASEAN-5 economies, an inverted U-shaped curve, suggesting that at lower (higher) level of financial development commensurate with higher (lower) level of tax evasion. One policy implication from this study is that the financial sector in ASEAN-5 economies can play an important role in reducing tax evasion by improving the accessibility to financing and to the credit market.